Fetishism and narcissism – the base of capitalism? - Jappe, Anselm (Estudios de Filosofía, 2020)
This article tries to resume Karl Marx’ concept of “commodity fetishism”, not just as a phenomenon of conscience, but as being the real heart of capitalist society based on abstract labor and value, money and commodity. This concept is often misunderstood, as well as the concept of “narcissism”. Following Freud and Christopher Lasch, the article underlines the sociological side of narcissism and how this pathology is the psychological counterpart to commodity fetishism, forming thus the typical subjectivity of consumerism.